RESPOSTAS DO FITOPLÂNCTON À PISCICULTURA EM TANQUES-REDE EM REPRESA DO SUDOES-TE DE MATO GROSSO DO SUL - Ismail, Yasser Adnan; ABELHA, Milza Celi Fedatto; BATISTA, Douglas Camargo; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2024)
-